Intimate partner violence and bystanders' helping behaviour: an experimental study. Issue 1 (27th July 2017) - Cinquegrana, Vincenza; Baldry, Anna Costanza; Pagliaro, Stefano
Abstract : Purpose: The purpose of this paper is to investigate the influence of contextual factors on the attribution of responsibility to female victims of an intimate partner violence (IPV) episode. The victim's infidelity and the perpetrator's alcohol abuse constituted the contextual factors in the investigation. The bystander's age, gender, and attitude towards gender roles were predicted to influence the attribution of responsibility to an IPV victim, and their willingness to help. Design/methodology/approach: An experimental study was conducted with 464 Italian participants with two independent conditions incorporated into a fictional scenario, measuring the different levels of the dependent variables under investigation. The participants were randomly assigned to different conditions provided their answers via an anonymous questionnaire. Findings: The participants attributed more responsibility to the victim when they admitted infidelity, controlling for gender role norms and sexism. Attribution of responsibility, male gender, and attitudes towards the male gender role were significantly associated with less willingness to help the victim. Practical implications: The results point to the importance of increasing the bystander's role in preventing IPV by addressing gender role norms and their impact on the justification of violence. Originality/value: The study complements the existing literature by providing new evidence of the barriers that prevent the bystander's intervention in IPV episodes. A clearer understanding of these barriers will help to develop strategies that aim to prevent violence in the future.